Self-Motion Perception Influences Postural Sway More than Environmental Motion Perception - Anson, Eric R; Critelli, Kyle; Chen, Edward; Staab, Jeffrey P; Carpenter, Mark G; Crane, Benjamin (bioRxiv, 2025)
Motion of the visual field can alter postural sway and cause illusions of self-motion. The relative perceptual sensitivity of self-motion versus visual field motion induced by virtual reality (VR) stimulation and whether observable sway differs based on perceptual task is unknown. Methods to quantify sway perception while concurrently measuring sway do not exist. We measured head sway and motion perception (self or world) in healthy adults who stood with feet together wearing a VR headset while experiencing adaptive staircases of virtual sinusoidal pitch rotation about the ankle axis. In separate conditions of randomly ordered blocks, subjects were asked to indicate (yes/no) if the room moved (regardless of perceived postural sway) or if their postural sway increased (regardless of perceived room motion). Head sway area was measured by tracking movement of the VR headset. Yes/No responses were fit with psychometric curves to determine points of subjective equality (PSEs) for room motion and postural sway. PSEs were compared between conditions. Effects of motion perception (binary responses) on head sway area before, during, and after visual stimulation were examined. The mean PSE for room motion (0.42 degrees) was significantly lower than for postural sway (2.02 degrees) [t(1,18) = 4.4714, p = 0.00029]. Head sway area was significantly larger during (z = 11.53, p < 0.001) and after (z = 5.09, p < 0.001) visual stimulation only when participants perceived increased postural sway. Nearly 5-fold greater amplitudes of oscillating VR visual stimuli were required to induce perceptions of altered self- versus visual field motion. Observed head sway during visual motion was only linked to perceptual responses when participants focused internally on self-motion, not externally on room motion.